The Role of Oral Isotretinoin in Thick Skin Rhinoplasty: A Systematic Review - Yip, Hao Meng; Fernandez-Carrera, Isabel; Chopra, Sunil; Paun, Santdeep (Facial Plastic Surgery, 2025)
Thick skin poses a challenge in rhinoplasty, often resulting in an undefined tip and supratip deformities.This study evaluates oral isotretinoin as an adjuvant treatment for thick-skinned rhinoplasty patients.This is a systematic review conducted in accordance with PRISMA guidelines.Two independent investigators performed a comprehensive literature search to identify studies that assessed perioperative oral isotretinoin treatment in thick skin rhinoplasty patients. Key outcome measures include skin thickness reduction, cosmetic surgical outcomes, and postoperative patient satisfaction.Five studies met the study inclusion criteria. Their findings demonstrated that oral isotretinoin effectively reduces skin thickness and improves cosmetic outcomes and satisfaction up to 6 months postoperatively, with no major complications reported.Although evidence is limited, oral isotretinoin shows promise in enhancing short-term rhinoplasty outcomes for thick-skinned patients. Further, high-quality trials are needed to confirm these results and develop standardized treatment protocols.
Keywords: isotretinoin; accutane; roaccutane; rhinoplasty; septorhinoplasty